2007
DOI: 10.1007/s10661-007-9617-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two metal surveys by moss Tortula ruralis in Budapest, Hungary

Abstract: Moss transplants of Tortula ruralis were used as active biomonitoring organisms as part of a monitoring study to assess the metals (Al, Cd, Cu, Cr, Fe, Ni, Pb, V and Zn) associated with ambient particles on mosses in Budapest, the capital town of Hungary. The moss samples were collected in a nature conservation area from a semi-arid sand grassland (Festucetum vaginatae danubiale), less than 1 month before transplantation. Moss cushions were exposed to pollution in Budapest during October-November 1993 and Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Metals, such as Pb, Cd, Cu, Cr, Ni, Zn, Sb and those from the platinum group, are released from motor vehicles and deposited on the roads and plants close to the road (Ho and Tai 1988, Legret and Pagotto 2006, Zechmeister et al 2006. Many studies have shown that urban soils and plants receive a considerable amount of trace metals mostly from motor vehicles (Biasioli et al 2006, Naszradi et al 2007, Oliva and Espinosa 2007. Vehicle exhausts are also considered to be a major source of atmospheric nitrogen (N) pollution in the form of nitrogen oxide (NO x ) emissions (Pearson et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Metals, such as Pb, Cd, Cu, Cr, Ni, Zn, Sb and those from the platinum group, are released from motor vehicles and deposited on the roads and plants close to the road (Ho and Tai 1988, Legret and Pagotto 2006, Zechmeister et al 2006. Many studies have shown that urban soils and plants receive a considerable amount of trace metals mostly from motor vehicles (Biasioli et al 2006, Naszradi et al 2007, Oliva and Espinosa 2007. Vehicle exhausts are also considered to be a major source of atmospheric nitrogen (N) pollution in the form of nitrogen oxide (NO x ) emissions (Pearson et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The microwave digestion equipped with temperature and pressure control assisted by common mineral acids, such as nitric, perchloric, and hydrochloric acids, is frequently used for sample digestion . Various techniques were employed for elemental analysis, namely, flame atomic absorption spectrometry (FAAS) , graphite furnace atomic absorption spectrometry (GFAAS) , cold vapor atomic absorption spectrometry (CVAAS) , , X-ray emission (PIXE) , , X-ray fluorescence (XRFS) , , inductively coupled plasma atomic emission spectrometry (ICP-AES) , and inductively coupled plasma optical emission spectrometry (ICP-OES) , . Besides those mentioned previously, many other techniques such as differential pulse cathode stripping voltamperometry (DPCSV) , have also been shown to be excellent tools for trace and ultratrace analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The moss species S. ruralis is according toHill et al (2007) sensitive to heavy metals but this species is widely spread all over Tallinn, registered also in the neighbourhood of roads with heavy traffic. Contrary to theHill et al (2007) work,Naszradi et al (2007) found S. ruralis (Tortula ruralis) to be a suitable moss for indication of heavy metal pollution due to its resistant nature against stress factors, including heavy metals. At the same time in theGilbert (1970) study S. ruralis was found much further (11.2 km) from the source of the pollution than C. purpureus and B. argenteum (1.6 km).…”
mentioning
confidence: 77%